Coated modified positive electrode material, preparation method thereof and secondary battery

By using the composite material of G-C3N4 and cobalt-doped calcium aluminum silicate to modify lithium-ion battery positive electrode materials, the existing positive pole materials are inadequate in energy density and cycle life, and achieve higher. Conductivity, stability and high magnification performance.

CN119381436APending Publication Date: 2025-01-28ZHUJI PAWA NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411597186.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have shortcomings in terms of energy density and cycle life, and it is difficult to meet the needs of high-performance lithium-ion batteries.

Method used

The composite material of the G-C3N4 and cobalt-doped calcium aluminum silicate is modified to the positive electrode materials. After the sintering composite material and the positive electrode material, the coating modifiers are formed.

Benefits of technology

It significantly improves the electrical, stability, and high -power performance of the positive pole material, thereby improving the energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381436A_ABST
    Figure CN119381436A_ABST
Patent Text Reader

Abstract

The invention provides a coated modified positive electrode material and a preparation method thereof, and a secondary battery, the coated modified positive electrode material comprises a positive electrode material and a composite material coating at least part of the surface of the positive electrode material, the composite material is a composite material of g-C3N4 and cobalt-doped calcium aluminosilicate, the mass ratio of the g-C3N4 to the cobalt-doped calcium aluminosilicate in the composite material is 1: (0.1-10). The positive electrode material is coated and modified by adopting a compound of g-C3N4 and cobalt-doped calcium aluminosilicate, so that the conductivity, the stability and the high-rate performance of the positive electrode material can be effectively improved, the energy density and the cycling stability of the battery are further remarkably improved, and a new technical path is provided for research and development of the high-performance lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials for lithium ion batteries, and in particular relates to the modification of positive electrode materials. Background Art

[0002] In recent years, with the rapid expansion of the electric vehicle market, the demand for high-performance lithium-ion batteries with high energy density and long cycle life has continued to grow. This trend has not only promoted breakthroughs in battery technology, but also accelerated the research and development of lithium-ion batteries with higher energy density, longer service life and higher safety. The conductivity and structural stability of lithium battery positive electrode materials are key factors that determine battery performance. In order to significantly improve the performance of positive electrode materials, doping and coating strategies play an important role in improving the conductivity and structural stability of materials, thereby improving the overall performance of batteries. Summary of the invention

[0003] In response to the above technical problems, the present application provides a coated modified positive electrode material and a preparation method thereof, and a secondary battery.

[0004] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a coated modified positive electrode material is provided, comprising a positive electrode material and a composite material coated on at least a portion of the surface of the positive electrode material, wherein the composite material is a composite material of g-C3N4 and cobalt-doped calcium aluminum silicate, and the mass ratio of g-C3N4 to cobalt-doped calcium aluminum silicate in the composite material is 1:0.1~10.

[0005] In a second aspect, a method for preparing a coated modified positive electrode material is provided, comprising: S1, mixing calcium aluminum silicate with a soluble cobalt salt solution, heating and stirring to obtain a solid mixture, and sintering the solid mixture to obtain cobalt-doped calcium aluminum silicate; S2, mixing g-C3N4 and cobalt-doped calcium aluminum silicate uniformly, and sintering to obtain a composite material; S3, mixing the composite material with the positive electrode material, and then sintering them to obtain a coated modified positive electrode material.

[0006] In a third aspect, a secondary battery is provided, comprising the aforementioned coated modified positive electrode material or the coated modified positive electrode material prepared by the aforementioned preparation method.

[0007] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The use of a composite of g-C3N4 and cobalt-doped calcium aluminum silicate to coat and modify the positive electrode material can effectively improve the conductivity, stability and high-rate performance of the positive electrode material, thereby significantly improving the energy density and cycle stability of the battery, providing a new technical path for the research and development of high-performance lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0009] Figure 1 This is the XRD pattern of the product prepared in step S1 of Example 1.

[0010] Figure 2 This is the SEM image of the product prepared in step S1 of Example 1.

[0011] Figure 3 This is the SEM image of the product prepared in step S2 of Example 1.

[0012] Figure 4 This is the Co element mapping diagram of the product prepared in step S2 of Example 1.

[0013] Figure 5 This is the XRD pattern of the product prepared in step S2 of Example 1.

[0014] Figure 6 This is the SEM image of the g-C3N4 material prepared in step S3 of Example 1.

[0015] Figure 7 This is a SEM image of the composite material prepared in step S4 of Example 1.

[0016] Figure 8 This is a SEM image of the positive electrode material prepared in step S5 of Example 1.

[0017] Fig. 9 This is a SEM image of the coated and modified positive electrode material prepared in step S6 of Example 1. DETAILED DESCRIPTION

[0018] The present invention provides a coated modified positive electrode material, comprising a positive electrode material and a composite material coated on at least a portion of the surface of the positive electrode material, wherein the composite material is a composite material of g-C3N4 and cobalt-doped calcium aluminum silicate, and the mass ratio of g-C3N4 to cobalt-doped calcium aluminum silicate in the composite material is 1:0.1~10.

[0019] The present invention utilizes the high thermal stability and chemical stability (poor conductivity) of calcium aluminum silicate and the conductivity and stability of g-C3N4 to improve the structural stability, thermal stability and cycle stability of the positive electrode material by coating; at the same time, in order to improve the composite coating effect, the calcium aluminum silicate is modified by cobalt doping, and the cobalt-doped and modified calcium aluminum silicate is sintered and composited with g-C3N4. On the one hand, the cobalt-doped and modified calcium aluminum silicate can significantly improve the interface compatibility between the calcium aluminum silicate and g-C3N4, improve the composite effect, and thus help to improve the electron and ion migration efficiency, as well as the stability under high-rate discharge and long life: ① Cobalt doping can refine the grains, increase the specific surface area of ​​the calcium aluminum silicate, increase the contact area between the doped calcium aluminum silicate and g-C3N4, and form a more stable interface structure; ② Cobalt doping helps to form a stronger chemical bond or physical interaction, promoting the close combination between the calcium aluminum silicate and g-C3N4 , thereby reducing interface defects and separation phenomena; ③ Due to the doping of cobalt, the electrical and chemical properties of calcium aluminum silicate may be closer to g-C3N4, thereby reducing the energy barrier at the interface and improving the electron transfer process; and the introduction of g-C3N4 enhances the interface characteristics between the two, promotes charge transfer, and thus improves the conductivity and chemical stability; this composite material combines their respective advantages and significantly improves the overall performance; on the other hand, cobalt doping can effectively improve the conductivity (enhance electron transfer efficiency) and structural stability of calcium cobalt silicate, and further improve the modification effect; therefore, the use of cobalt-doped calcium aluminum silicate composite g-C3N4 to coat the ternary positive electrode material can have a synergistic effect, which can effectively improve the conductivity, stability and high-rate performance of the positive electrode material. The combination of this composite and coating technology significantly improves the energy density and cycle stability of the battery, and provides a new technical path for the research and development of high-performance lithium-ion batteries.

[0020] In some preferred embodiments, in the composite material, the mass ratio of g-C3N4 to cobalt-doped calcium aluminum silicate is 1:0.5~2, for example, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, etc.

[0021] In some preferred embodiments, in the composite material, g-C3N4 and cobalt-doped calcium aluminum silicate are uniformly distributed.

[0022] In some preferred embodiments, the mass ratio of the composite material to the positive electrode material is 1~10wt.%:1, and more preferably 1~6wt.%:1, for example 1wt.%:1, 1.5wt.%:1, 2wt.%:1, 2.5wt.%:1, 3wt.%:1, 3.5wt.%:1, 4wt.%:1, 4.5wt.%:1, 5wt.%:1, 5.5wt.%:1, 6wt.%:1, etc.

[0023] In some preferred embodiments, the cobalt doping amount in the cobalt-doped calcium aluminum silicate is 1~10wt.%, for example, 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, etc.

[0024] In some embodiments, the positive electrode material may be a NCM ternary positive electrode material. However, in fact, the positive electrode material may be a conventional lithium-ion battery positive electrode material in the art. The positive electrode material for lithium-ion batteries includes but is not limited to NCM / NCA ternary positive electrode materials, lithium iron phosphate, lithium iron manganese phosphate, lithium-rich manganese-based positive electrode materials, lithium cobalt oxide, spinel lithium manganese oxide, molybdenum sulfide, polyanion positive electrode materials (Na x M y (XO4) n , wherein M is a transition metal (such as Fe, Mn, Ni, Cu, V, etc.), X is S, P, Si, Mo, As, etc.), vanadium oxide, sulfide positive electrode material, lithium vanadium phosphate, silicon-based / silicon oxygen positive electrode material, lithium vanadium oxide, etc., which can be homemade or purchased. The homemade ones can be prepared by conventional preparation methods in the art.

[0025] The present invention also provides a method for preparing a coated modified positive electrode material, comprising: S1, mixing calcium aluminum silicate with a soluble cobalt salt solution, heating and stirring to obtain a solid mixture, and sintering the solid mixture to obtain cobalt-doped calcium aluminum silicate; S2, mixing g-C3N4 and cobalt-doped calcium aluminum silicate uniformly, and sintering to obtain a composite material; S3, mixing the composite material with the positive electrode material, and then sintering them to obtain a coated modified positive electrode material.

[0026] In some preferred embodiments, in step S1, the sintering temperature is 300-800°C, for example, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc.; the sintering time is 0.5-10h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0027] In some preferred embodiments, the cobalt doping amount in the cobalt-doped calcium aluminum silicate is 1~10wt.%, for example, 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, etc.

[0028] In some preferred embodiments, the soluble cobalt salt is a cobalt salt that can be thermally decomposed into oxides; the cobalt salt that can be thermally decomposed into oxides is selected from one or more of cobalt nitrate and organic cobalt salts; the organic cobalt salt can be, for example, cobalt acetate or its hydrate.

[0029] In some preferred embodiments, in step S2, the sintering temperature is 300-800°C, for example, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc.; the sintering time is 0.5-10h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0030] In step S2, the uniform mixing can be achieved by conventional mixing methods in the art, such as mechanical ball milling or solution blending.

[0031] In some preferred embodiments, the mass ratio of g-C3N4 to cobalt-doped calcium aluminum silicate is 1:0.1~10, and more preferably 1:0.5~2.

[0032] In some preferred embodiments, in step S3, the sintering temperature is 300-700°C, for example, 300°C, 400°C, 500°C, 600°C, 700°C, etc.

[0033] In some preferred embodiments, the mass ratio of the composite material to the positive electrode material is 1:10-100, for example, 1:10, 1:12.5, 1:15, 1:20, 1:30, 1:40, 1:50, 1:100, etc.

[0034] In some preferred embodiments, the preparation method of the calcium aluminum silicate comprises: dissolving a calcium source, an aluminum source, an organic silicon source and a complexing agent in a solvent, stirring the reaction to obtain a sol, drying the sol to obtain a gel, and sintering the gel to obtain the calcium aluminum silicate. Using the prepared calcium aluminum silicate is beneficial to improving its surface activity and improving the subsequent cobalt doping.

[0035] In some preferred embodiments, the sintering temperature of the gel is 300-800°C, more preferably 400-700°C, for example, 400°C, 500°C, 600°C, 700°C, etc.; the sintering time of the gel is 1-9 h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, etc.

[0036] In some preferred embodiments, the calcium source is one or more of calcium nitrate, calcium acetate, calcium citrate, and calcium carbonate.

[0037] In some preferred embodiments, the aluminum source is one or more of aluminum nitrate, aluminum acetate, sodium aluminate, aluminum hydroxide, and amino acid aluminum complex.

[0038] In some preferred embodiments, the organic silicon source is one or more of tetraethoxysilane, trimethylsilane, triethylaminosilane, trichloroethylsilane, trimethoxysilane, a silane coupling agent, and polydimethylsiloxane.

[0039] In some preferred embodiments, the complexing agent is one or more of citric acid, oxalic acid, oxalic acid, tartaric acid, EDTA, aminotriacetic acid, dopamine, and malic acid.

[0040] In some preferred embodiments, the calcium source, aluminum source and organic silicon source are mixed in a molar ratio of Ca, Al and Si of 3:2:3.

[0041] In some preferred embodiments, the molar ratio of the calcium source to the complexing agent is 1:0.8 to 1:1.2.

[0042] In some embodiments, the g-C3N4 can be prepared by conventional preparation methods in the art; specifically, it can be prepared by thermal decomposition of melamine; the thermal decomposition temperature is 400~800℃, for example, 400℃, 500℃, 600℃, 700℃, 800℃, etc.; the thermal decomposition time is 1~5 h, for example, 1h, 2h, 3h, 4h, 5h, etc.

[0043] In some embodiments, the g-C3N4 is obtained by pyrolyzing melamine and then grinding it into a micron size.

[0044] The present invention also provides a secondary battery, comprising the aforementioned coated modified positive electrode material.

[0045] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0046] Example 1 Preparation of cobalt-doped calcium aluminum silicate composite g-C3N4 coated positive electrode material, including: Step S1: Preparation of calcium aluminum silicate Take Ca(NO3)2·4H2O (corresponding to 0.03 molCa 2+ )、Al(NO3)3·9H2O(corresponding to 0.02 molAl 3+) and tetraethoxysilane (TEOS, corresponding to 0.03 mol Si) were dissolved in 50 mL of a water / ethanol mixed solution (the volume ratio of water to ethanol was 1:4) at a molar ratio of 3:2:3 and stirred evenly; 1.92 g of citric acid (corresponding to 0.01 mol) was dissolved in 20 mL of water, and after preparing a solution, it was added dropwise to the mixed solution, and stirring was continued until a sol was formed, and the sol was dried at 80 ° C for 12 hours to obtain a gel. The gel was then pre-sintered in air at 600 ° C for 2 hours to obtain calcium aluminum silicate. The XRD pattern of the obtained calcium aluminum silicate is shown as follows Figure 1 As shown, from Figure 1 It can be seen that the preparation of Ca3Al2(SiO4)3 was successfully achieved, and the SEM image of the obtained calcium aluminum silicate is as follows Figure 2 shown.

[0047] Step S2: Preparation of cobalt-doped calcium aluminum silicate Calcium aluminum silicate was mixed with a cobalt salt (Co(NO3)2·6H2O) solution to uniformly dope cobalt ions into the calcium aluminum silicate matrix. The cobalt doping amount was 5wt.%; after the mixture was dried, it was sintered at 500°C in an air atmosphere for 3 hours to obtain a cobalt-doped calcium aluminum silicate material. The SEM image is shown in FIG. Figure 3 As shown, the cobalt element mapping diagram is as follows Figure 4 As shown, from Figure 4 It can be seen that the Co element is mapped on the silicate surface, indicating that the Co element is doped into the material; the XRD pattern of the obtained cobalt-doped calcium aluminum silicate material is as follows Figure 5 As shown, from Figure 5 It can be seen that no impurity phase appears, further confirming that Co doping has been achieved.

[0048] Step S3: Preparation of carbon trinitrogen tetrakis(g-C3N4) Take a certain amount of melamine and pyrolyze it in air at 550℃ for 2 hours to obtain g-C3N4 powder. The powder is ground to obtain g-C3N4 material with a particle size of micrometers. The SEM image is as follows: Figure 6 As shown, from Figure 6 The lamellar structure can be clearly seen.

[0049] Step S4: Preparation of Co-doped Calcium Aluminum Silicate and g-C3N4 Composite Material After weighing 0.5 g of g-C3N4 powder and 0.5 g of cobalt-doped calcium aluminum silicate in a mass ratio of 1:1, g-C3N4 was added to 50 mL of ethanol and ultrasonically dispersed for 30 minutes to form a uniform suspension; then, cobalt-doped calcium aluminum silicate was added to the g-C3N4 suspension, and ultrasonically stirred again for 30 minutes to fully mix the two; finally, the mixed solution was dried at 80°C to obtain a mixed powder, and the mixed powder was sintered at 500°C for 5 hours to form a composite material of cobalt-doped calcium aluminum silicate and g-C3N4, the SEM image of which is shown in FIG. Figure 7 shown.

[0050] Step S5: Preparation of positive electrode materials The nickel-cobalt-manganese ternary precursor (NCM, Ni 0.9 Co 0.05 Mn 0.05 (OH)2) and lithium hydroxide were mixed in a molar ratio of 1:1.05 and uniformly mixed using a ball mill; the mixture was placed in a high-temperature furnace and sintered at 750°C for 28 hours to obtain a nickel-cobalt-manganese ternary positive electrode material (LiNi 0.9 Co 0.05 Mn 0.05 O2), its SEM picture is as follows Figure 8 shown.

[0051] Step S6: Preparation of coated positive electrode material The prepared positive electrode material was mixed with cobalt-doped calcium aluminum silicate composite g-C3N4 material in a mass ratio of 10:0.2, and sintered at 500°C in air atmosphere for 5h to obtain a coated modified positive electrode material, the SEM image of which is shown in FIG. Fig. 9 As shown, from Fig. 9 It can be seen that there are small particles on the surface of the material, confirming that coating has been achieved.

[0052] Comparative Example 1 Preparation of cobalt-doped calcium aluminum silicate coated positive electrode material, comprising: Step S1: Preparation of calcium aluminum silicate Take 0.03molCa(NO3)2·4H2O, 0.02molAl(NO 3)3 9H2O and 0.03 mol tetraethoxysilane (TEOS) were dissolved in 50 mL of a water / ethanol mixed solution (the volume ratio of water to ethanol was 1:4) in a molar ratio of 3:2:3, and stirred evenly. 1.92 g of citric acid (corresponding to 0.01 mol) was dissolved in 20 mL of water, and the solution was added dropwise to the mixed solution. The stirring was continued until a sol was formed. The sol was dried at 80°C to obtain a gel, and the gel was pre-sintered at 600°C for 2 hours to obtain calcium aluminum silicate.

[0053] Step S2: Preparation of cobalt-doped calcium aluminum silicate Calcium aluminum silicate and cobalt salt (Co(NO3)2·6H2O) solution were mixed to uniformly dope cobalt ions into the calcium aluminum silicate matrix. The cobalt doping amount was 5wt.%. After the mixture was dried, it was sintered at 500°C in an air atmosphere for 3 hours to obtain a cobalt-doped calcium aluminum silicate material.

[0054] Step S3: Preparation of positive electrode materials The nickel-cobalt-manganese ternary precursor (NCM, Ni 0.9 Co 0.05 Mn 0.05 (OH)2) and lithium hydroxide were mixed in a molar ratio of 1:1.05 and uniformly mixed using a ball mill; the mixture was placed in a high-temperature furnace and sintered at 750°C for 28 hours to obtain the original nickel-cobalt-manganese ternary positive electrode material (LiNi 0.9 Co 0.05 Mn 0.05 O2).

[0055] Step S4: Preparation of cobalt-doped calcium aluminum silicate coated positive electrode material The cobalt-doped calcium aluminum silicate material and the prepared positive electrode material were mixed at a mass ratio of 0.2:10. The mixture was sintered at 500° C. in an air atmosphere for 5 hours to obtain a positive electrode material coated and modified by the cobalt-doped calcium aluminum silicate material.

[0056] Comparative Example 2 Preparation of g-C3N4 coated positive electrode material, including: Step S1: Preparation of g-C3N4 Take a certain amount of melamine, heat it to 550°C in air, and keep it for 2 hours for thermal decomposition to obtain g-C3N4 powder; grind the powder to obtain g-C3N4 material with a particle size of micrometer level.

[0057] Step S2: Preparation of positive electrode materials The nickel-cobalt-manganese ternary precursor (NCM) and lithium hydroxide were mixed in a molar ratio of 1:1.05, and the mixture was evenly mixed using a ball mill. The mixture was placed in a high-temperature furnace and sintered at 750°C for 28 hours to obtain the original nickel-cobalt-manganese ternary positive electrode material (LiNi 0.9 Co 0.05 Mn 0.05 O2).

[0058] Step S3: Preparation of g-C3N4 coated positive electrode material The g-C3N4 powder was mixed with the prepared positive electrode material in a mass ratio of 0.2:10, and the mixture was sintered at 500° C. in an air atmosphere for 5 h to obtain a g-C3N4 coated and modified positive electrode material.

[0059] Comparative Example 3 Preparation of aluminosilicate coated positive electrode material, comprising: Step S1: Preparation of calcium aluminum silicate Take a certain amount of Ca(NO3)2·4H2O, Al(NO 3)3 9H2O and tetraethoxysilane (TEOS) are dissolved in a water / ethanol mixed solution according to a certain molar ratio, and stirred evenly. Citric acid is added dropwise to the solution as a complexing agent, and stirring is continued to form a sol. The sol is dried at 80°C to obtain a gel, and the gel is pre-sintered at 600°C for 2 hours to obtain calcium aluminum silicate.

[0060] Step S2: Preparation of positive electrode materials The nickel-cobalt-manganese ternary precursor (NCM, Ni 0.9 Co 0.05 Mn 0.05 (OH)2) and lithium hydroxide were mixed in a molar ratio of 1:1.05, and the mixture was evenly mixed using a ball mill. The mixture was placed in a high-temperature furnace and sintered at 750°C for 28 hours to obtain the original nickel-cobalt-manganese ternary positive electrode material (LiNi 0.9 Co 0.05 Mn 0.05 O2).

[0061] Step S3: Preparation of calcium aluminum silicate coated positive electrode material The calcium aluminum silicate material and the prepared positive electrode material were mixed in a mass ratio of 0.2:10, and the mixture was sintered at 500° C. in an air atmosphere for 5 hours to obtain a calcium aluminum silicate coated modified positive electrode material.

[0062] Comparative Example 4 Preparation of calcium aluminum silicate and g-C3N4 composite coated positive electrode material, including: Step S1: Preparation of calcium aluminum silicate Take 0.03molCa(NO3)2·4H2O, 0.02molAl(NO 3)3 9H2O and 0.03 mol tetraethoxysilane (TEOS) were dissolved in 50 mL of a water / ethanol mixed solution (the volume ratio of water to ethanol was 1:4) in a molar ratio of 3:2:3, and stirred evenly. 1.92 g of citric acid (corresponding to 0.01 mol) was dissolved in 20 mL of water, and the solution was added dropwise to the mixed solution. The stirring was continued until a sol was formed. The sol was dried at 80°C to obtain a gel, and the gel was pre-sintered at 600°C for 2 hours to obtain calcium aluminum silicate.

[0063] Step S2: Preparation of g-C3N4 Take a certain amount of melamine, heat it to 550°C in air, keep it for 2 hours for thermal decomposition, and obtain g-C3N4 powder. Grind the powder to obtain g-C3N4 material with a particle size of micrometer level.

[0064] Step S3: Preparation of calcium aluminum silicate and g-C3N4 composite material Calcium aluminum silicate and g-C3N4 are mixed in a mass ratio of 1:1, and the two are uniformly mixed using a mechanical ball milling method or a solution blending method.

[0065] Step S4: Preparation of positive electrode materials The nickel-cobalt-manganese ternary precursor (NCM, Ni 0.9 Co 0.05 Mn 0.05 (OH)2) and lithium hydroxide were mixed in a molar ratio of 1:1.05 and uniformly mixed using a ball mill; the mixture was placed in a high-temperature furnace and sintered at 750°C for 28 hours to obtain the original nickel-cobalt-manganese ternary positive electrode material (LiNi 0.9 Co 0.05 Mn 0.05 O2).

[0066] Step S5: Preparation of coated positive electrode material The prepared calcium aluminum silicate and g-C3N4 composite was mixed with the positive electrode material at a mass ratio of 0.2:10. The mixture was sintered at 500° C. in an air atmosphere for 5 h to obtain a composite coated modified positive electrode material.

[0067] Comparative Example 5 The nickel-nickel-cobalt-manganese ternary precursor (NCM, Ni 0.9 Co 0.05 Mn 0.05 (OH)2) and lithium hydroxide were mixed in a molar ratio of 1:1.05, and a ball mill was used to evenly mix the mixture. The mixture was placed in a high-temperature furnace and sintered at 750°C for 28 hours to obtain the original nickel-cobalt-manganese ternary positive electrode material (LiNi 0.9 Co 0.05 Mn 0.05 O2).

[0068] Example 2 The only difference between this embodiment and embodiment 1 is that in step S2, the doping amount of cobalt is 1 wt.%.

[0069] Example 3 The only difference between this embodiment and embodiment 1 is that in step S2, the doping amount of cobalt is 3 wt.%.

[0070] Example 4 The only difference between this embodiment and embodiment 1 is that in step S6, the positive electrode material and the cobalt-doped calcium aluminum silicate composite g-C3N4 material are mixed in a mass ratio of 10:0.4, and sintered at 500°C in an air atmosphere for 5 hours to obtain a coated modified positive electrode material.

[0071] Example 5 The only difference between this embodiment and embodiment 1 is that in step S6, the positive electrode material and the cobalt-doped calcium aluminum silicate composite g-C3N4 material are mixed in a mass ratio of 10:0.1, and sintered at 500°C in an air atmosphere for 5 hours to obtain a coated modified positive electrode material.

[0072] Preparation of button cells: The positive electrode materials prepared in Examples 1 to 5 and the positive electrode materials prepared in Comparative Examples 1 to 5 were mixed with Super-P, KS-6 and polyvinylidene fluoride (PVDF) in a mass ratio of 89:5:3.5:2.5 in N-methyl-2-pyrrolidone (NMP) to prepare a uniform positive electrode slurry. The prepared positive electrode slurry was evenly coated on aluminum foil, and a fast coating machine was used to ensure uniform coating, and then dried under a vacuum environment of 120°C for 2 hours to ensure that NMP was completely volatilized and a dry positive electrode material layer was obtained to obtain a positive electrode sheet. The positive electrode sheet was cut into discs (12 mm diameter) suitable for button batteries, and then button batteries were assembled in a glove box with an Ar gas atmosphere. The metal lithium sheet was used as the negative electrode; the lithium ion secondary electrolyte LB-037 (1M LiPF6in DEC:EC:EMC (volume ratio) = 1:1:1) was used as the electrolyte, and Celgard2325 was used as the diaphragm to assemble a button battery. The charge and discharge tests were carried out on the Blue Electric test system, with the test temperature at 25°C and the test voltage range of 3~4.3V.

[0073] As can be seen from Table 1, the cobalt-doped calcium aluminum silicate composite g-C3N4 coated positive electrode material prepared in each embodiment has a higher specific capacity than the positive electrode material prepared in the comparative example, and has better rate performance and cycle performance. After analysis, the reasons for this phenomenon include the following: On the one hand, cobalt-doped modified calcium aluminum silicate can significantly improve the interface compatibility between calcium aluminum silicate and g-C3N4, improve the composite effect, and thus help to improve the efficiency of electron and ion migration, as well as stability under high-rate discharge and long life: ① Cobalt doping can refine the grains, increase the specific surface area of ​​calcium aluminum silicate, increase the contact area between doped calcium aluminum silicate and g-C3N4, and form a more stable interface structure; ② Cobalt doping helps to form stronger chemical bonds or physical interactions, promotes close bonding between calcium aluminum silicate and g-C3N4, thereby reducing interface defects and separation phenomena; ③ Due to cobalt doping, calcium aluminum silicate The electrical and chemical properties of g-C3N4 may be closer to those of g-C3N4, thereby reducing the energy barrier at the interface and improving the electron transfer process; and the introduction of g-C3N4 enhances the interface characteristics between the two, promotes charge transfer, and thus improves the conductivity and chemical stability; this composite material combines the advantages of each other and significantly improves the overall performance; on the other hand, cobalt doping can effectively improve the conductivity (enhance electron transfer efficiency) and structural stability of calcium cobalt silicate, and further improve the modification effect; therefore, the use of cobalt-doped calcium aluminum silicate composite g-C3N4 to coat the ternary positive electrode material can have a synergistic effect, which can effectively improve the conductivity, stability and high-rate performance of the positive electrode material.

[0074] Table 1 Example 6 The only difference between this embodiment and embodiment 1 is that in step S4, the mass ratio of g-C3N4 powder to cobalt-doped calcium aluminum silicate is 1:0.5.

[0075] Example 7 The only difference between this embodiment and embodiment 1 is that in step S4, the mass ratio of g-C3N4 powder and cobalt-doped calcium aluminum silicate is 1:2.

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Coated modified positive electrode material, characterized in that: It comprises a positive electrode material and a composite material coated on at least a portion of the surface of the positive electrode material, wherein the composite material is a composite material of g-C3N4 and cobalt-doped calcium aluminum silicate, and the mass ratio of g-C3N4 to cobalt-doped calcium aluminum silicate in the composite material is 1:0.1~10.

2. The coated modified positive electrode material according to claim 1, characterized in that: In the composite material, the mass ratio of g-C3N4 to cobalt-doped calcium aluminum silicate is 1:0.5-2; In the composite material, g-C3N4 and cobalt-doped calcium aluminum silicate are uniformly distributed; The mass ratio of the composite material to the positive electrode material is 1-10wt.%:1, more preferably 1-5wt.%:1; In the cobalt-doped calcium aluminum silicate, the doping amount of cobalt is 1-10wt.%; The positive electrode material is a ternary positive electrode material for a lithium-ion battery.

3. A method for preparing a coated modified positive electrode material, characterized in that: include: S1, mixing calcium aluminum silicate with a soluble cobalt salt solution, heating and stirring to obtain a solid mixture, and sintering the solid mixture to obtain cobalt-doped calcium aluminum silicate; S2, mixing g-C3N4 and cobalt-doped calcium aluminum silicate uniformly, and sintering to obtain a composite material; S3, mixing the composite material with the positive electrode material, and then sintering them to obtain a coated modified positive electrode material.

4. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: In step S1, the sintering temperature is 300-800°C; the sintering time is 0.5-10h.

5. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: In the cobalt-doped calcium aluminum silicate, the doping amount of cobalt is 1-10wt.%; The soluble cobalt salt is a cobalt salt that can be thermally decomposed into oxides; the cobalt salt that can be thermally decomposed into oxides is selected from one or more of cobalt nitrate and organic cobalt salts.

6. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: In step S2, the sintering temperature is 300-800°C; the sintering time is 0.5-10h; The mass ratio of the g-C3N4 to the cobalt-doped calcium aluminum silicate is 1:0.1~10, and more preferably 1:0.5~2.

7. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: In step S3, the sintering temperature is 300-700° C. and the sintering time is 3-7 hours. The mass ratio of the composite material to the positive electrode material is 1:10-100.

8. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: The preparation method of the calcium aluminum silicate comprises: dissolving a calcium source, an aluminum source, an organic silicon source and a complexing agent in a solvent, stirring and reacting to obtain a sol, drying the sol to obtain a gel, and sintering the gel to obtain the calcium aluminum silicate.

9. The method for preparing a coated modified positive electrode material according to claim 4, characterized in that: The temperature of the sintering gel is 300-800°C; the time of the sintering gel is 1-9 hours; The calcium source is one or more of calcium nitrate, calcium acetate, calcium citrate and calcium carbonate; The aluminum source is one or more of aluminum nitrate, aluminum acetate, sodium aluminate, aluminum hydroxide, and amino acid aluminum complex; The organic silicon source is one or more of tetraethoxysilane, trimethylsilane, triethylaminosilane, trichloroethylsilane, trimethoxysilane, silane coupling agent, and polydimethylsiloxane; The complexing agent is one or more of citric acid, oxalic acid, oxalic acid, tartaric acid, EDTA, aminotriacetic acid, dopamine, and malic acid; The calcium source, aluminum source and organic silicon source are mixed in a molar ratio of Ca, Al and Si of 3:2:3; The molar ratio of the calcium source to the complexing agent is 1:0.8 to 1:1.

2.

10. A secondary battery, characterized in that: It includes the coated modified positive electrode material as described in claim 1 or 2 or the coated modified positive electrode material prepared by the preparation method as described in any one of claims 3 to 9.

Citation Information

Cited By

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and electrochemical device

    CN121672460A